Time-domain response of linear hysteretic systems to deterministic and random excitations. - Muscolino, G.
The causal and physically realizable Biot hysteretic model proves to be the simplest linear model able to describe the nearly rate independent behaviour of engineering materials. In this paper, the performance of the Biot hysteretic model is analysed and compared with those of the ideal and causal hysteretic models. The Laguerre polynomial approximation (LPA) method, recently proposed for the time domain analysis of linear viscoelastic systems, is then summarized and applied to the prediction of the dynamic response of linear viscoelastic systems, is then summarized and applied to the prediction of the dynamic response of linear viscoelastic systems, is then summarized and applied to the prediction of the dynamic response of linear hysteretic systems to deterministic and random excitations. The parameters of the LPA model generally need to be computed through numerical integrals; however, when this model is used to approximate the Biot hysteretic model, closed-form expressions can be found. Effective step by step procedures are also provided in the paper, which prove to be accurate also for high levels of damping. Finally, the method is applied to the dynamic analysis of a highway embankment excited by deterministic and random ground motions. The results show that in some cases the inaccuracy associated with the use of an equivalent viscous damping model is too large.
Keywords: Linear hysteretic damping; Biot model; Laguerre polynomial approximation; Seismic analysis; Random vibration; Earth structures